Lãnh đạo phi chính thức: Yếu tố thúc đẩy sự thành công của nhóm ảo - Nguyễn Quang, Anh; Huỳnh Trọng , Hiến; Nguyễn Hoàng, Phúc; Lương Bích, Ân; Trần Diễm , Quỳnh; Nguyễn Thị Hương, Giang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
As virtual teamwork becomes increasingly common, the lack of direct interaction poses significant challenges in communication and coordination among team members. In this context, informal leadership emerges as a crucial factor in building trust, fostering cohesion, and helping the team overcome obstacles. This study not only explores the core competencies of informal leaders in an online environment but also analyzes their impact on team performance. Additionally, it provides practical solutions for businesses to create a supportive work environment, train and develop skills for informal leaders, thereby enhancing work productivity and team cohesion. These findings lay the groundwork for future research in the field of organizational behavior in within teams.